(untitled) (Medical Forum Monthly, 2024)
Background: Leprosy is a chronic infectious disease that, inspite of its ancient origin, still affects thousands of people throughout the world. It is caused by Mycobacterium leprae, which mainly affects the skin and peripheral nerves, leading to sensory loss in the skin, muscle weakness and often permanent disabilities of hands and feet. Leprosy is now known to be neither sexually transmitted nor highly infectious after treatment. Approximately 95% of people are naturally immune and sufferers are no longer infectious after as little as 2 weeks of treatment It is completely curable by using multi drug therapy. Mycobacterium leprae was discovered in 1873, by G. H. Armauer Hansen in Norway, therefore leprosy is referred as Hansen's disease. It is a mutilating, debilitating, devastating and deforming disease. Objective: To evalualate the lipid profile in leprosy cases and compare them with healthy control subjects. Study Design: Case Control Study. Place and Duration of Study: Present study was carried out in the Department of Biochemistry, Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre, Karachi, in collaboration with Marrie Adelaide Leprosy Centre (National Training Institute of Leprosy Control Programme), Karachi from June 2009 to May 2011. Materials and Methods: A total of 60 newly diagnosed leprosy patients of both sexes and all ages were included in this study, among them 44 males and 16 females, aged 13 to 70 years (mean 37.8 ± 1.71 years). The diagnosis were on clinical ground and bacterial examination by slit skin smear test and 30 age, sex matched healthy control subjects were taken from general population for comparison. Informed consent was taken from each patient and control subject for this study. Results: All the lipid fractions except HDL cholesterol were decreased significantly high (p<0.01) where as HDL Cholesterol was increased significantly (p<0.05) in leprosy patients when compared with control group. In present study total cholesterol was 127.1 ± 1.46 mg % , Triglyceride 111.7 ± 1.68 mg % , HDL Cholesterol 45.4 ± 0.89 mg % and LDL Cholesterol 80.2 ± 1.72 mg % in leprosy subjects. Conclusion: It is concluded that, all the lipid fractions except HDL cholesterol were decreased significantly high , where as HDL Cholesterol was increased significantly in leprosy patients when compared with control group, which are in favour of lepers.